Laryngeal Inflammatory Pseudotumour Secondary to Mycobacterium kansasii - Saif Al-Zahid; Tanwen Wright; Philip Reece (Case Reports in Pathology)
Background. Inflammatory pseudotumours (IPT) are rare benign tumours characterised by spindle-shaped histiocyte proliferation often mimicking a soft tissue sarcoma. They can occur in different parts of the body and various aetiological factors have been proposed. To our knowledge this is the first case report of IPT of the larynx caused by mycobacterial disease. Case Report. We report a case of IPT of the larynx in an immunocompromised 81-year-old lady presenting with stridor and dysphagia with known disseminated Mycobacterium kansasii of the lungs. Conclusion. This case demonstrates both the clinical and histological difficulties in making the diagnosis of IPT. A high index of suspicion is needed, and the importance of a multidisciplinary approach in the work-up, diagnosis, and management is highlighted.